Developing Ecofeminist Theory - Cudworth, E. author. aut Link
IX, 218 p.
Keywords: An original exploration of how the relationship between society and 'nature' is conceptualized, focusing on theories of social exclusion and difference. A comprehensive overview of feminist and environmental theories of society-environment relations, considering the range of theoretical and political influences on such theorizing such as socialist and Marxist theory amongst others and the turn to post structuralism and postmodernism within the social sciences. Cudworth also develops her own theoretical account for the interrelations between forms of social domination and contributes to important debates with sociology, social theory, feminist theory and environmentalism.